SIRKULASI ELIT POLITIK LOKAL PADA PILKADA SERENTAK TAHUN 2015 DI PROVINSI JAMBI - Farisi, Mochammad (JISIP UNJA (Jurnal Ilmu Sosial Ilmu Politik Universitas Jambi), 2017)
Direct election of regional heads (Pilkada) conducted simultaneously on December 9, 2015 has become a new model of local political elite circulation in the area of ​​democratic system implementation. Pilkada directly provides an opportunity for the community to elect its future leaders with qualified lead candidates requires a transparent and democratic recruitment process. A qualified recruitment process will produce regional heads with integrity. The regulation has stipulated that a political party or a coalition of political parties is an institution that has the function of selecting or recruiting prospective leaders to be offered to the public, so it must be a concern for political parties to always carry out the process accountably and democratically.The purpose of this study is to know; System and selection of recruitment of political parties in determining pairs of candidates for head of region and Know how the circulation of political elites that occurred in Pilkada Serentak 2015 in Jambi. This research uses descriptive qualitative approach with party chairman, candidate of head of region or team of winner from both political party, and commissioner of KPUD as informans. The results is the 2015 electoral contest consisted of one governor election and four bupati elections and one mayor namely Bungo Regency, Batang Hari Regency, East Tanjung Jabung Regency, Tanjung Jabung Barat Regency and Sungai Penuh City the process of recruitment of candidates for heads of regions all political parties rely on survey services so that only candidates with high popularity and elektabilitas course which became the benchmark party in determining the candidate pair. The loss of dynastic political rules in regulation also adds to the exclusivity of the circulation of local political elites.